2011
DOI: 10.1038/bmt.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CD34+ peak in peripheral blood during mobilization in intermediate-risk AML patients treated in first CR by autologous or allogeneic transplantation

Abstract: Ninety-six AML patients in 1st CR were evaluated for peak CD34 þ cell levels in peripheral blood (PB) during PBSC mobilization and harvest. Distribution of CD34 þ cell peaks was determined and cases were grouped on the basis of 50th and 75th percentile: group A, those having a CD34 þ cell peak p70 Â 10 9 /L (n ¼ 48); group B, those having a CD34 þ cell peak between 70 and 183 Â 10 9 /L (n ¼ 24); group C, those having a CD34 þ cell peak 4183 Â 10 9 /L (n ¼ 24). Irrespective of post-remission treatment received,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For CD34 + stem cell dose, many data showed that excessive amount of autologous stem cell infusion was associated with higher relapse rate, because it might be related with graft contamination of leukemic cells [35,42,43]. Similarly, other reports also revealed that good mobilization during PBSC collection was a significant factor for more relapse and poorer DFS compared with poor mobilization [44][45][46]. We also identified that CD34 + stem cell dose higher than 4.5 × 10 6 /kg was associated with more relapse, but good mobilization (35.4% versus 25.2%, P = .764) or using auto-PBSC collected from first consolidation therapy (31.1% versus 27.2%, P = .436) were not studied.…”
Section: Discussionmentioning
confidence: 99%
“…For CD34 + stem cell dose, many data showed that excessive amount of autologous stem cell infusion was associated with higher relapse rate, because it might be related with graft contamination of leukemic cells [35,42,43]. Similarly, other reports also revealed that good mobilization during PBSC collection was a significant factor for more relapse and poorer DFS compared with poor mobilization [44][45][46]. We also identified that CD34 + stem cell dose higher than 4.5 × 10 6 /kg was associated with more relapse, but good mobilization (35.4% versus 25.2%, P = .764) or using auto-PBSC collected from first consolidation therapy (31.1% versus 27.2%, P = .436) were not studied.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar attempt to establish individual prognostic tools, Milone et al [28] analyzed 96 AML patients in CR1 for peak CD34 þ cell levels in PB during PBSC mobilization and harvest, irrespective of postremission treatment received. The peak of CD34 þ cells in PB was an independent predictor for DFS in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This cut-off was selected based on the range of levels (between 50,000 and 100,000 CD34+ cells/ml) described in the literature available at the start of this analysis [6,7,9,11]. …”
Section: Methodsmentioning
confidence: 99%
“…We found that patients mobilizing more than 60,000 CD34+ cells per ml of peripheral blood at the day of apheresis had decisively shorter time to progression and overall survival. This cut-off was selected based on previous reports proposing levels between 50,000 and 100,000 CD34+ cells/ml [6,7,9,11]. (16)), intermediate-risk (normal karyotype; −Y); very bad-risk (MK+: two or more different autosomal chromosome monosomies or a single autosomal monosomy combined with one or more structural chromosome abnormalities), and bad-risk AML (MK−: all others).…”
Section: Introductionmentioning
confidence: 99%